Effectivity of Bacillus thuringiensis from Soil in Freshwater Swamps against Epilachna sp. Larvae - Yulia Pujiastuti; Erni Indriani; A Muslim; Chandra Irsan; Arsi Arsi (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2021)
Bacillus thuringiensis is an entomopathogenic bacterium isolated from the soil and has been widely used as an active ingredient in the manufacture of bioinsecticides. The target insects are very specific and depend on the type of protein content. Epilachna sp. are important insect pests because both larvae and adults as plant-eating pests. The research aimed was to investigate the effectivity of B. thuringiensis against the larvae of Epilachna sp.. B. thuringiensis- bio-insecticide was prepared using isolates originally from freshwater swamp soil of South Sumatra (SMR04). Epilachna sp larvae were mass-reared with Solanum torvum leaf feed in the laboratory. The design used was a completely randomized design, with 6 treatments and 5 replications. Treatments were spore concentration contained in the bioinsecticide solution included: 1 x 108, 1 x 107, 1 x 106, 1 x 105 spores/mL, commercial bio-insecticide and without treatment as a control. Each replication used 10 individual of the 2nd larvae. Statistical test results showed larval mortality in B. thuringiensis treatment was significantly different from commercial bio-insecticide treatment. The highest mortality of bio-insecticide treatment occurred at a concentration of 108 spores/ml (40.00 %) and the lowest was at a concentration of 105 spores/mL (18.01 %). The lowest LT50 value of bio-insecticide treatment was at a concentration of 108 spores/mL, namely 79.37 hours. The control of larvae included in the Coleoptera order was still not satisfactory yet, considering the presence of protein content in B. thuringiensis strain SMR04 which did not match the type of protein required.